The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1021/jp910472c
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Based Studies on the Nature of Raman and Resonance Raman Scattering of Nerve Agent Bound to Gold and Oxide-Supported Gold Clusters: A Plausible Way of Detection

Abstract: A detailed theoretical investigation has been carried out at the density functional level of theories to investigate the nature of Raman intensities of the -P=O stretching mode of a model nerve agent DFP (diisopropylfluorophosphate) when bound to different gold (Au(8), Au(20)) and oxide-supported gold (MgO...Au(4), CaO...Au(4), TiO(2)...Au(4), Al(2)O(3)...Au(4), M(16)O(16)...Au(8), and [M(16)O(15)...Au(8)](2+), M = Ca, Mg) clusters. All of these clusters and the DFP-bound clusters are fully optimized, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Raman spectroscopy has been particularly used in determining the lattice dynamics and crystallinity of several materials, such as carbon-based, , metal oxides, , and polymers. , Raman spectroscopy can also be used in a time-resolved manner to track the structural changes under in situ conditions . In particular, Raman has been useful in identifying structures, vibrational modes and molecular conformations, as well as bond orientations of organophosphorus compounds in their pure form or when adsorbed onto surfaces. Depending on the excitation energies, laser power, signal-to-noise ratio, and integration time, many fingerprint regions could be distinguished. , For example, Choi et al showed, using principal component analysis applied to Raman spectra, that nerve agents with similar molecular structures can be easily distinguished . Wang et al.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Raman spectroscopy has been particularly used in determining the lattice dynamics and crystallinity of several materials, such as carbon-based, , metal oxides, , and polymers. , Raman spectroscopy can also be used in a time-resolved manner to track the structural changes under in situ conditions . In particular, Raman has been useful in identifying structures, vibrational modes and molecular conformations, as well as bond orientations of organophosphorus compounds in their pure form or when adsorbed onto surfaces. Depending on the excitation energies, laser power, signal-to-noise ratio, and integration time, many fingerprint regions could be distinguished. , For example, Choi et al showed, using principal component analysis applied to Raman spectra, that nerve agents with similar molecular structures can be easily distinguished . Wang et al.…”
Section: Raman Spectroscopymentioning
confidence: 99%